The effect of antioxidants on post-thawed Angora goat (Capra hircus ancryrensis) sperm parameters, lipid peroxidation and antioxidant activities - Bucak, Mustafa Numan; Sarioezkan, Serpil; Tuncer, Puerhan Barbaros; Sakin, Fatih; Atessahin, Ahmet; Kulaksiz, Recai; Cevik, Mesut (Elsevier Science Bv, 2010)
The aim of this study was to determine the effects of the antioxidants curcumin, inositol and carnitine on microscopic seminal parameters, lipid peroxidation (LPO) and the antioxidant activities of sperm, following the freeze-thawing of Angora goat semen. Ejaculates were collected via artificial vagina from three Angora goats and microscopically evaluated and pooled at 37 degrees C. The pooled semen samples were diluted in a Tris-based extender, including curcumin (2.5, 5 or 10 mM), inositol (2.5, 5 or 10 mM), carnitine (2.5, 5 or 10 mM) and no antioxidant (control). The diluted semen was slowly (at a rate of 0.2-0.3 degrees C/min) cooled to 5 degrees C and then cryopreserved in 0.25 mL French straws. Frozen straws were thawed individually at 37 degrees C for 20s in a water bath, for microscopic sperm evaluation. The freezing extender supplemented with 2.5 mM curcumin led to higher percentage of computer-assisted semen analyzer (CASA) sperm motility (65 +/- 3%), when compared to the control, inositol and the 10 mM carnitine (P<0.01) groups, following the freeze-thawing process. The addition of antioxidants did not provide any significant effect on the percentages of post-thaw subjective analyses and CASA progressive motilities, as well as sperm motility characteristics (VAP, VSL, LIN and ALH), compared to the controls. Freezing extenders with antioxidants at three different doses led to lower percentages of acrosome and total sperm abnormalities, when compared to the controls (P<0.001). However, the addition of 5 mM inositol did not induce any difference in total sperm abnormalities, when compared to the controls. The antioxidants also did not show any effectiveness in the elimination of malondialdehyde (MDA) formation and the maintenance of glutathione peroxidase (GSH-PX) activity, when compared to the controls. Superoxide dismutase (SOD) activity was found to be higher in the presence of curcumin at all three dose levels and carnitine at 5 mM, compared to the other groups. Glutathione (GSH) concentration was demonstrated to be maintained at a higher level with the addition of inositol, compared to the other groups. However, these differences in SOD and GSH levels were not significant, compared to the controls. All the antioxidants at all three dose levels resulted in a better protection of the sperm morphology (except for 5 mM inositol with respect to the total sperm abnormalities), compared to the control samples. According to CASA, the best post-thawing sperm motility rate was recorded when the freezing extender was supplemented with 2.5 mM curcumin. Further studies are required to obtain more conclusive results regarding the characterization of microscopic and oxidative stress parameters in cryopreserved goat sperm, using the different antioxidants. Crown Copyright (C) 2009 Published by Elsevier B.V. All rights reserved.
Keywords: Angora goat sperm; Antioxidants; Sperm parameters; Lipid peroxidation; Antioxidant activity